Efektivitas Biokoagulan Serbuk Kulit Pisang Kepok dan Biji Jarak Pagar terhadap Kadar COD Air Limbah Domestik - Apriliya Thalib; Herlina Jusuf; Tri Septian Maksum (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Domestic wastewater is liquid waste generated by various human activities, including households, offices, and other public facilities. The liquid waste produced generally has a relatively high Chemical Oxygen Demand (COD) concentration. The use of biocoagulants such as kepok banana peel powder and physic nut seeds is a new alternative for environmentally friendly, efficient wastewater treatment. This study aims to test the effectiveness of utilizing kepok banana peel powder and physic nut seeds as biocoagulants in reducing COD levels of domestic wastewater. This study employed a true experimental design with a Completely Randomized Design (CRD), using dose ratios of 25%:75%, 50%:50%, and 75%:25% with three repetitions. The domestic wastewater sample consisted of 5 liters obtained using the Grab Sample technique. Data were analyzed using the One-Way ANOVA test with a significance level (a) of 5%. The study results show that the biocoagulant combination of kepok banana peel powder and physic nut seeds is effective in reducing COD levels. The initial COD level of the domestic wastewater was 1870 mg/L. The most effective dose ratio for reducing COD levels was 25%:75%, with an effectiveness of 24%. In conclusion, there is a difference in the effectiveness of the combination of kepok banana peel powder and physic nut seeds in reducing COD levels in domestic wastewater (p-value=0.000). The community is encouraged to utilize biocoagulant powder derived from kepok banana peel waste and physic nut seeds as an alternative for more environmentally friendly domestic wastewater treatment.